(Ine)quality of life: Lithuanian labor migration to Sweden during the economic crisis and its aftermath, 2008–2013. Issue 1 (2nd January 2019) - Genelyte, Indre
ABSTRACT: This article connects micro and macro scales of inequality to Lithuanians' decisions to depart to Sweden during the economic crisis with austerity measures and its aftermath (2008–2013). This period revealed unequal opportunities regarding the quality of life that were largely created by the gradual re-commodification of labor as well as unaddressed income and social inequalities which had existed since the 1990s. Nevertheless, macro inequalities did not directly lead to the exit decision. Rather, this was bound to the individual's perception of the leaving opportunity and (possible) quality of life for oneself and one's family across time and space.